DEVELOPING SKILLS TO IMITATE SHAPES USING PROJECT BASED LEARNING MODELS, EXPLICIT INSTRUCTION, AND FLANNEL MEDIA IN THE B1 GROUP OF BAKTI 1 ISLAMIC KINDERGARTEN BANJARMASIN - Khalifah, Lutpia; Permatasari, Nina (E-CHIEF Journal, 2024)
The purpose of the study is to describe teacher activities, children's skills, and children's developmental outcomes in imitating shapes. This research approach uses qualitative with the type of classroom action research, carried out in 4 meetings, the research setting is on the B1 group of children of Bakti 1 Islamic Kindergarten Banjarmasin which amounted to 14 children (9 boys and 5 girls). The data collection technique uses observation. The results of the study showed that (1) the teacher's activity at the 1st meeting received a score of 20 in the "Good" category and continued to increase until the 4th meeting received a score of 27 in the "Very Good" category. (2) Children's Skills in the 1st meeting got a percentage of 0% in the category "No Skilled Children" and continued to increase until the 4th meeting with a percentage of 100% in the category "All Active Children". (3) The results of the development of the ability to imitate shapes at the 1st meeting were 0% and continued to increase at the 4th meeting the score of 100% all children succeeded in developing in the category of "Developing as Expected (BSH), and Developing Very Well (BSB)". Based on the results of the study, it can be concluded that  the Project Based Learning, Explicit Instruction and Media Flanel models can develop skills, and the results of the development of the ability to imitate children's shapes very well and all children are active